Fun-Ing: Applying a Playful and Embodied Pedagogical Approach to an Online Poetry Workshop in the Mobile Arts for Peace Project - Sarah Huxley (International Journal of Contemporary Educational Research)
This paper presents how a playful and embodied educational approach (fun-ing) (xxxx, 2023) was applied to an international online poetry workshop for young people to foreground qualities of learning experience, rather than outcomes alone. The methodology of fun-ing is grounded in a reflexive and emplaced ethnographic approach (Pink, 2011), in which the performing body-mind is perceived as encountering its surroundings and the material elements (living/non-living). By applying the Six Guiding Principles of fun-ing (xxxx, 2023), to design and analyse an online poetry workshop, organised as part of the xxx AHRC-funded project, the paper shows that the principles, originally derived from a doctoral study, can be used in other non-formal learning contexts. The principles are a useful tool to support creative educationalists to shape joyful and novel learning experiences. Ultimately, the paper calls for further contextually specific adaptations of the fun-ing principles by educationalists, artists, and researchers alike.